5z+8z=Z-2-9z

Simple and best practice solution for 5z+8z=Z-2-9z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z+8z=Z-2-9z equation:


Simplifying
5z + 8z = Z + -2 + -9z

Combine like terms: 5z + 8z = 13z
13z = Z + -2 + -9z

Reorder the terms:
13z = -2 + Z + -9z

Solving
13z = -2 + Z + -9z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '9z' to each side of the equation.
13z + 9z = -2 + Z + -9z + 9z

Combine like terms: 13z + 9z = 22z
22z = -2 + Z + -9z + 9z

Combine like terms: -9z + 9z = 0
22z = -2 + Z + 0
22z = -2 + Z

Divide each side by '22'.
z = -0.09090909091 + 0.04545454545Z

Simplifying
z = -0.09090909091 + 0.04545454545Z

See similar equations:

| 10=5+v | | 8x+9=6x+32 | | -5/4x-2=-8 | | 2(6)+4y=24 | | y=1/2cos2x | | -20=1/3n-10 | | 212-3=53 | | 2(4)+4y=24 | | 3/50=x/5280 | | (1/65)=(1/x) | | 1+2r+8r=1+7r+8+4 | | y+26=-5 | | 5x+4x=40 | | 6b+10b-7= | | 10n-3=-2 | | 2(x+7)+x=6x+10 | | 72+x-x^2=0 | | 2(2)+4y=24 | | 6(3-4n)-3n=18 | | 24-6r=6[4-r] | | 25y+5x=30yx | | 14x+16=9x+14+52 | | 2(1)+4y=24 | | x^3-7x^2-8x=2 | | 20x=x^2+5 | | 2x(x+7)+x=6x+10 | | 7/5000=x/78000 | | x^3-7x^2-8x+2=0 | | 5[y-2]-2=2[y+1]-5 | | 8x+2=2x-7x | | 6x+8=2+3x+5x | | -4.7x=-10.81 |

Equations solver categories